PEMBERDAYAAN MASYARAKAT MELALUI POLA PADAT KARYA TUNAI DESA (PKTD) DARI DANA DESA DI DESA CIPAKAT KECAMATAN SINGAPARNA KABUPATEN TASIKMALAYA - Dandan Haryono; Evi Silviana (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
Cipakat Village, Singaparna Subdistrict, Tasikmalaya District, two main issues have been identified: target inaccuracy and insufficient community awareness regarding this program. The aim of this research is to assess the effectiveness of Community Empowerment through the Cash for Work Program (PKTD) funded by the Village Fund in Cipakat Village, Singaparna Subdistrict, Tasikmalaya District. The research methodology employed is descriptive research with a qualitative approach. Data collection methods include interviews, observations, and document analysis. The research findings and analysis indicate that the Location Selection dimension has not been implemented effectively, and the dimension of Socialization has also been poorly executed. However, the Empowerment Process dimension has been executed effectively, as well as the dimension of Community Empowerment towards self-sufficiency. In conclusion, the stages of empowerment show that only two out of the four empowerment stages have been executed effectively, namely the empowerment process and community self-sufficiency. Meanwhile, the other two empowerment stages, namely location selection and socialization, have not been executed effectively. Therefore, it can be deemed as ineffective.